Fibro-Adipogenic Progenitors: Versatile keepers of skeletal muscle homeostasis, beyond the response to myotrauma. (November 2021) - Wei, X.; Nicoletti, C.; Puri, P.L.
Abstract: While Fibro-Adipogenic Progenitors (FAPs) have been originally identified as muscle-interstitial mesenchymal cells activated in response to muscle injury and endowed with inducible fibrogenic and adipogenic potential, subsequent studies have expanded their phenotypic and functional repertoire and revealed their contribution to skeletal muscle response to a vast range of perturbations. Here we review the emerging contribution of FAPs to skeletal muscle responses to motor neuron injuries and to systemic physiological (e.g., exercise) or pathological metabolic (e.g., diabetes) perturbations. We also provide an initial blueprint of discrete sub-clusters of FAPs that are activated by specific perturbations and discuss their role in muscle adaptation to these conditions.